Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Dengan Harga Sebagai Variabel Moderating Pada PT. Perdana Agro Mandiri - Irfan Febrianto; Wardayani Wardayani (CIVITAS: Jurnal Studi Manajemen, 2022)
This study aims to determine whether there is an effect of product quality and promotion on purchasing decisions simultaneously and partially, and to find out how price moderates product quality and promotion on purchasing decisions at PT Perdana Agro Mandiri for the period January-July 2020. The results showed that the coefficient of determination test (R2) obtained results of 0.807 or 80.7% indicating that product quality and promotion variables were able to explain the variations that occurred in the purchasing decisions of PT. Perdana Agro Mandiri, while the remaining 19.3% is explained by other variables not examined. The results of the study partially and significantly affected product quality on purchasing decisions, while promotions had no effect and were not significant on purchasing decisions at PT. Prime Agro Mandiri. While the simultaneous product quality and promotion have a positive and significant impact on purchasing decisions at PT. Prime Agro Mandiri. And Moderated Regression Analysis (MRA) shows that price does not moderate product quality and promotion on purchasing decisions at PT. Prime Agro Mandiri.